2021
DOI: 10.1109/trpms.2020.3020212
|View full text |Cite
|
Sign up to set email alerts
|

Photon Counting CT: Clinical Applications and Future Developments

Abstract: The use of a photon counting detector in CT (PCD CT) is currently the subject of intense investigation and development. In this review article, we will describe potential clinical applications of this technology with a particular focus on the experience of our own institution with a prototype PCD CT scanner. Photon counting detectors (PCDs) have three primary advantages over conventional, energy integrating detectors (EIDs): 1) they provide spectral information without need for a dedicated dual-energy protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 104 publications
0
76
0
1
Order By: Relevance
“…Photon-counting detectors not only allow for the simultaneous acquisition of multiple energy bins but also provide a variety of other benefits. Popular examples include but are not limited to a reduction in radiation and contrast media dose [32][33][34]. Hence, our experiments provide guidelines for threshold settings maximizing image quality in iodine maps, even if a dual-energy decomposition is only performed retrospectively.…”
Section: Discussionmentioning
confidence: 98%
“…Photon-counting detectors not only allow for the simultaneous acquisition of multiple energy bins but also provide a variety of other benefits. Popular examples include but are not limited to a reduction in radiation and contrast media dose [32][33][34]. Hence, our experiments provide guidelines for threshold settings maximizing image quality in iodine maps, even if a dual-energy decomposition is only performed retrospectively.…”
Section: Discussionmentioning
confidence: 98%
“…Medical imaging technology plays a great role in disease diagnosis, in which computed tomography (CT) imaging is widely used in clinical medicine [ 7 ]. At present, the three-dimensional reconstruction of skull CT data is usually carried out in the research on the relationship between bony orbital changes and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline restoration would suppress dynamic noise floor fluctuations and affect the output of low-energy windows. (5) This study was conducted with a sufficiently large number of counts per reading recorded. The condition was chosen to make the CRLB analysis valid: It has been shown that if only a few counts on average per reading were recorded, the asymptotic property of maximum-likelihood would not hold and estimated results might be biased, 46 which in turn, would violate the foundation of the CRLB analysis: the existence of an unbiased estimator.…”
Section: Discussionmentioning
confidence: 99%